Prevalence of hypoglycemic conditions in adolescents with type 1 diabetes mellitus in real clinical practice - I. M. Tsargasova; E. B. Bashnina; N. V. Vorokhobina; T. A. Dubinina; E. R. Dosovitskaya; V. V. Platonov (Сахарный диабет)
BACKGROUND. Hypoglycemia and fear of hypoglycemia remain critical problems in the treatment of adolescents with type 1 diabetes mellitus (DM1) and are factors limiting proper control of glycemia and preventing the achievement of metabolic compensation of the disease. The use of pump insulin therapy involves the prevention of hypoglycemic conditions.AIM. To analyze the frequency and duration of hypoglycemia episodes, their effect on the metabolic compensation of the disease in adolescents with type 1 diabetes mellitus (DM1) in real clinical practice, depending on the mode/method of insulin administration.MATERIALS AND METHODS. The study involved 117 adolescents with DM1 aged 12 to 19 years (average age 15.5 years). 37 adolescents received therapy by continuous subcutaneous insulin infusion (CSII); 80 adolescents received therapy by multiple insulin injections (MII). The level of glycated hemoglobin (HbA1c) was determined for all adolescents, and its main indicators were evaluated using a 6 days continuous glucose monitoring (CGM) by the «blind» method of a professional system with an iPro 2 sensor (Medtronic MiniMed, USA).RESULTS. Episodes of a decrease in glucose levels <3,9 mmol/l were recorded in 87% of patients (n=102), 63% (n=74) showed a decrease in glucose levels <3,0 mmol/l. Episodes decrease in glucose levels <3,9 mmol/l at night were recorded in 68% of patients (n=80), and with glucose levels <3,9 mmol/l in 46% (n=54). The frequency of episodes of glucose lowering <3,9 mmol/l had no statistically significant differences depending on the methods of insulin administration (by continuous subcutaneous insulin infusion or multiple insulin injections), however, they are more common in adolescents with HbA1c <7,0% (p=0,03). The median time spent by patients in the range of <3,9 mmol/l was 5% per day, and a longer time in this range was observed in patients with HbA1c <7,0% (p=0,006). The median time in the range of <3,0 mmol/l was 1% per day and had no significant differences depending on the level of HbA1c (p=0,559). There were also no significant differences depending on the groups using CSII and MII (p=0,640 and p=0,250).CONCLUSION. Episodes of glucose reduction in the range of <3,9 mmol/l according to CGM data are more common in adolescents with HbA1c target values, regardless of the method of insulin administration. Significantly more time in range of <3,9 mmol/l is spent by adolescents with target values of HbA1c i.е. <7,0% compared with HbA1c ≥7,0%, however, in both groups, a large number of patients had time in the range below the target level was higher than recommended values.